2000
DOI: 10.1007/s005920070030
|View full text |Cite
|
Sign up to set email alerts
|

Intensive insulin therapy combined with metformin in obese type 2 diabetec patients

Abstract: Unlike other pharmacological therapies used in obese type 2 diabetic patients, metformin has been shown to improve glycemic control with lower insulin levels and not to involve weight gain. We therefore examined the effect of adjunct metformin in 13 severely obese type 2 diabetic patients (BMI 39.3 +/- 3.9 kg/m2) in suboptimal glycemic control pretreated with intensified insulin therapy. Patients were randomly assigned to either metformin or placebo treatment (double-blind) for 10 weeks and after a 2 week wash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
7

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 8 publications
3
15
0
7
Order By: Relevance
“…We are aware of a study (31) finding no change in either basal or stimulated levels of C peptide in a group of hypertensive patients after metformin. In a group of obese type 2 diabetics an increase in C peptide levels after metformin treatment was found (32). These discrepancies are difficult to explain and deserve further research.…”
Section: ) Although Not With Those Obtained By Others (12± 15)mentioning
confidence: 91%
“…We are aware of a study (31) finding no change in either basal or stimulated levels of C peptide in a group of hypertensive patients after metformin. In a group of obese type 2 diabetics an increase in C peptide levels after metformin treatment was found (32). These discrepancies are difficult to explain and deserve further research.…”
Section: ) Although Not With Those Obtained By Others (12± 15)mentioning
confidence: 91%
“…A number of these trials, listed in Table 2, 54-66 demonstrated significant reductions in body weight between patients receiving insulin and metformin compared with insulin and placebo 54,56,59,60,62 although other studies did not. 55,57,58,61,63,64 Two trials demonstrated Figure 1 Effects of randomized treatments on body weight in overweight patients in the UK Prospective Diabetes Study. 31 …”
Section: Metformin and Weight A Golaymentioning
confidence: 99%
“…Es existiert eine Reihe von Publikationen über deren Wirksamkeit in Bezug auf HbA1c-Senkung (effektiver als Insulin allein), Nüchterblutzuckersen-kung und insulinsparendem Effekt [22]. Die Gabe von Metformin zur Nacht (Suppression der nächt-lichen Glukoneogenese) in Kombination mit Insulin ist v. a. für adipöse Patienten mit ausgeprägter Insulinresistenz geeignet [23], da sich in dieser Kombination neben einem positiven Effekt auf die Stoffwechseleinstellung Insulin einsparen lässt und der Gewichtsverlauf positiv beeinflusst wird [24]. Auch die Kombination mit α-Glukosidase-Hemmern erscheint für adipöse Typ-2-Diabetiker mit ausgeprägter Insulinresistenz sinnvoll.…”
Section: Mischinsulineunclassified